Strategi Pemuridan Tuhan Yesus Sebagai Model Pelayanan Guna Meningkatkan Pertumbuhan Gereja - Suryanto (Sekolah Tinggi Teologi Borneo, 2023)
Abstract:The discipleship strategy of the Lord Jesus as a service model to increase growth in the Indonesian Methodist Church Imanuel Denpasar congregation. The purpose of writing is to explain the application of the discipleship model of the Lord Jesus. What is meant by growth in the Indonesian Methodist Church Imanuel Denpasar congregation is the increase in the number of church visitors on a regular basis from congregation members who are no longer enthusiastic about coming to church, people who were previously unchurched, or at least those who have not visited church for a long time because they do not have a church to visit every Sunday, or maybe they are an Atheist, maybe they also come from another faith.The type of research used is based on qualitative methods, namely data collected by observation and interviews. This research uses descriptive techniques, namely describing, or describing in sentences.The research uses qualitative research methods based on literature (library research). The author collects data from the literature that talks about the pattern of Jesus' ministry, especially Jesus' task which is to seek and save sinners. Data collection, also obtained from observation or observation of symptoms that occur in the lives of believers.The research found that discipleship is very good and very necessary, namely so that the congregation not only makes itself a listener, but also prepares the congregation to become an actor of the truth in the Bible. Through the discipleship of the Lord Jesus, the disciples are growing towards a good maturity of faith. With the implementation of discipleship for the congregation, the visible results are reflected in their daily life behavior. Such as diligent worship, diligent Bible reading, prayer, perseverance in hope, and care for others.Keywords: Discipleship model, JesusAbstrak:Strategi pemuridan Tuhan Yesus sebagai model pelayanan guna meningkatkan pertumbuhan di gereja Methodist Indonesia jemaat Imanuel Denpasar. Tujuan penulisan adalah untuk memaparkan penerapan model pemuridan Tuhan Yesus. Yang dimaksud pertumbuhan di gereja Methodist Indonesia jemaat Imanuel Denpasar yakni pertambahan jumlah pengunjung gereja secara tetap dari anggota jemaat yang sudah tidak semangat untuk datang kegereja, orang-orang yang sebelumnya tidak bergereja, atau setidaknya mereka yang sudah lama tidak mengunjungi gereja karena tidak memiliki gereja yang dikunjungi setiap Minggunya, atau mungkin mereka adalah seorang Atheis, mungkin juga mereka berasal dari iman yang lainJenis penelitian yang digunakan yaitu berdasarkan metode kualitatif yakni data yang dikumpulkan dengan observasi dan wawancara. Penelitian ini menggunakan teknik deskriptifyaitu menguraikan, atau memaparkan dalam kalimat.Penelitian menggunakan metode penelitian kualitatif berdasarkan kepustakaan (library research). Penulis mengumpulkan data-data dari pustaka yang berbicara mengenai pola pelayanan Yesus, khususnya tugas Yesus yang diemban-Nya yakni mencari dan menyelamatkan yang berdosa. Pengumpulan data, juga diperoleh dari observasi atau pengamatan terhadap gejala yang terjadi dalam kehidupan orang percaya.Penelitian ditemukan bahwa, pemuridan sangat baik dan sangat diperlukan, yaitu agar jemaat bukan saja menjadikan dirinya sebagai pendengar saja, melainkan juga disiapkan jemaat untuk menjadi pelaku pelaku kebenaran yang ada di dalam Alkitab. Melalui pemuridan Tuhan Yesus murid-murid semakin hari bertumbuh kearah kedewasaan iman yang baik. Dengan diadakannya pemuridan bagi jemaat maka hasil yang terlihat, yaitu terpancar dalam perilaku kehidupannya sehari-hari. Seperti rajin beribadah, rajin membaca Alkitab, berdoa, bertekun dalam pengharapan, dan peduli terhadap sesamanya.Kata kunci: Model pemuridan, Yesus